Nitrate-Enhanced NHC-NiH Catalyzed Tail-to-Tail Vinyl Ether Dimerization - He, Lisi; Ho, Chun-Yu (Synlett, 2014)
The first tail-to-tail vinyl ether dimerization has been developed by using a newly identified synergistic effect between the NHC-NiH catalyst and organonitrate additive (PhNO2 or t-BuNO2). The additive enhanced the desired C–C bond-forming reactivity by a proposed competitive coordination with the alkoxyl group of the hydrometallated vinyl ether species to the Ni center. This combination addressed complications related to β-alkoxy (β-OR) elimination and polymerization, and gave unexpected dimerization regioselectivity.
Keywords: N-heterocyclic carbenes; hydroalkenylation; nitrate additive; unsaturated ethers; nickel hydride